Disclosing the Redox Pathway Behind the Excellent Performance of CuS in Solid‐State Batteries. Issue 12 (4th November 2022) - Mullaliu, Angelo; Hosseini, Seyed Milad; Conti, Paolo; Aquilanti, Giuliana; Giorgetti, Marco; Varzi, Alberto; Passerini, Stefano
Abstract: Copper sulfide has attracted increasing attention as conversion‐type cathode material for, especially, solid‐state lithium‐based batteries. However, the reaction mechanism behind its extraordinary electroactivity is not well understood, and the various explanations given by the scientific community are diverging. Herein, the CuS reaction dynamics are highlighted by examining the occurring redox processes via a cutting‐edge methodology combining X‐ray absorption fine structure spectroscopy, and chemometrics to overcome X‐ray diffraction limitations posed by the poor material's crystallinity. The mathematical approach rules out the formation of intermediates and clarifies the direct conversion of CuS to Cu in a two‐electron process during discharge and reversible oxidation upon delithiation. Two distinct voltage regions are identified corresponding to Cu‐ as well as the S‐redox mechanisms occurring in the material. Abstract : This work investigates the reaction dynamics of copper sulfide in a solid‐state cell using an advanced spectroscopic/chemometric methodology. Extended X‐ray absorption fine structure spectra provide structural insight into the modifications around copper atoms, while the direct and reversible conversion of CuS to metallic copper is observed, clarifying the mechanism behind the excellent electrochemical performance.